2021
DOI: 10.3389/fpls.2021.651341
|View full text |Cite
|
Sign up to set email alerts
|

High Salinity Reduces Plant Growth and Photosynthetic Performance but Enhances Certain Nutritional Quality of C4 Halophyte Portulaca oleracea L. Grown Hydroponically Under LED Lighting

Abstract: Portulaca oleracea L. (known as purslane) is one of the most nutritious leafy vegetables owing to its high content of antioxidants. In this study, all plants were grown indoors hydroponically with different NaCl salinities. Photosynthetic photo flux density (PPFD) at 200 μmol m−2 s−1 (12 h) was provided to all plants by LED with red:blue ratio of 2.2. Thirty days after transplanting, plants grown with100 mM NaCl had the highest productivity and the fastest leaf growth followed by those with 0, 200 and 300 mM N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 96 publications
(163 reference statements)
6
38
2
Order By: Relevance
“…In our experiment, in contrast, TPC and TAC was not affected by salinity, and TFC was decreased when microgreens were grown with 80 mM NaCl (Table 2). However, in agreement with our results, He et al [5] revealed that purslane grown with 0 and 100 mM NaCl had similar TPC, which decreased when plants were grown with 200 and 300 mM NaCl. According to the previous authors, TPC for purslane grown under higher salinity could be associated with their lower photosynthetic performance, although genetics and environment can be also affecting their accumulation [64].…”
Section: Total Phenol Content Total Flavonoids Content and Total Antioxidant Capacitysupporting
confidence: 93%
See 3 more Smart Citations
“…In our experiment, in contrast, TPC and TAC was not affected by salinity, and TFC was decreased when microgreens were grown with 80 mM NaCl (Table 2). However, in agreement with our results, He et al [5] revealed that purslane grown with 0 and 100 mM NaCl had similar TPC, which decreased when plants were grown with 200 and 300 mM NaCl. According to the previous authors, TPC for purslane grown under higher salinity could be associated with their lower photosynthetic performance, although genetics and environment can be also affecting their accumulation [64].…”
Section: Total Phenol Content Total Flavonoids Content and Total Antioxidant Capacitysupporting
confidence: 93%
“…Accordingly, it was previously shown that purslane plants (cv. POR-2936) exposed to 100 mM NaCl presented higher shoot and root productivity, as compared to those grown with 0 mM NaCl [5]. However, the growth of an Aegean purslane accession was more suppressed under 140 mM NaCl than 70 mM NaCl [32], suggesting that the salinity concentration threshold to affect growth differs for each genotype [33].…”
Section: Yieldmentioning
confidence: 92%
See 2 more Smart Citations
“…With regard to the NO 3 content in lettuce, the maximum limits prescribed by European Union for lettuce produced in open field are 2,500-4,000 mg kg −1 fresh weight (FW) and for lettuce produced in the greenhouse are 3,500-4,500 mg kg −1 grown (Zhong et al, 2002). In the recent study with a nutritious leafy halophyte vegetable, Portulaca oleracea L (known as purslane) grown hydroponically, we have found that the NO 3 concentrations of purslane grown with 0, 100, 200, and 300 mM NaCl were 1,868, 2,081, 1,381, and 1,235 mg kg −1 FW, respectively (He et al, 2021b). However, for M. crystallinum plants grown under the same conditions, we have yet to determine the NO 3 concentrations in their edible shoots.…”
Section: Introductionmentioning
confidence: 90%